Effect of 17α-Methyltestosterone Hormone Manipulation in Various Water Temperatures on Sex Ratio of Guppy (Poecilia reticulata Peters) - Arfah, H.; Kadriah, A.K.; Carman, O. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This study was conducted to determine percentage of male progeny of guppy (Poecila reticulata Peters) broodstock immersed in water containing various dose of 17α-Methyltestosterone (MT) and different temperature. Immersion of broodstock was carried out at 10th day after spawning. Dosage of MT used was 0, 0.5 and 1 mg per liter of water, while the water temperature was 27, 30 and 33oC, for 24 hours immersion. The result of study showed that the combination of hormone treatment 1mg/L and temperature 27oC produced higher percentage of male progeny (92.7%). Increasing water temperature in combination with dose of hormone treatment can reduce percentage of male progeny. Keywords: guppy, Poecilia reticulata, 17α-Methyltestosterone, temperature, sex reversal, monosex ABSTRAK Penelitian ini dilakukan untuk mengetahui nisbah kelamin jantan keturunan induk ikan gapi (Poecila reticulata Peters) yang telah direndam hormon 17α-Metiltestosteron (MT) dengan berbagai tingkatan dosis yang dikombinasikan dengan temperatur air yang berbeda-beda. Perendaman induk dilakukan pada hari kesepuluh setelah pemijahan. Dosis hormon yang digunakan adalah 0, 0,5 dan 1 mg/L air, sementara suhu air perendaman adalah 27oC, 30oC dan 33oC, dengan lama perendaman 24 jam. Hasil penelitian menunjukkan bahwa kombinasi perlakuan hormon 1 mg/L dengan temperatur 27ºC menghasilkan rataan persentase ikan gapi kelamin jantan tertinggi yaitu 92,7%. Peningkatan temperatur yang dikombinasikan dengan dosis hormon ternyata mengakibatkan penurunan persentase anak berkelamin jantan. Kata kunci: ikan gapi, Poecilia retiulata, 17α-Metiltestosteron, temperatur, seks reversal, monoseks